SYNONYMS, ANTONYMS, HOMONYMS IN ENGLISH - Xaitkulova Arjuman (TADQIQOTLAR, 2026)
Abstract The English language contains a wide range of lexical relationships that contribute to its richness and flexibility. Among these, synonyms, antonyms, and homonyms are fundamental in understanding how meaning is constructed and interpreted. This article provides a detailed analysis of these three categories, including their definitions, types, functions, and roles in communication. By examining their semantic and practical significance, the article highlights how mastery of these relationships enhances vocabulary acquisition, linguistic competence, and effective communication in both spoken and written English.